New Qualities of Personal Identity in Virtual Reality (on the example of Armenian Facebook users) - Petrosyan, David (Bulletin of Yerevan University B: Philology, 2022)
The article presents the features of formation of personal identity in virtual reality. In the context of the comparative characteristics of real and virtual identities, special attention has been paid to the activities of the Armenian users on the social network “Facebook”. In their transformations of virtual identity (socializing on a single platform, aspirations for self-assertion in network reality, idealization of biographical identity, etc.), a number of direct and indirect manifestations of national identity, psychology and character are obvious.